Effect of pH on Adsorption of Cu2+ by Using Composite of Polyvinyl Alcohol (PVA)/Kaolin - Hassim, N.A.A. (Gadjah Mada University, 2022)
The existence of copper ions in the aquatic environment at a high level can cause negative repercussions for living organisms due to the toxic effect of bioaccumulation in the food chain. Hence, a profound effort is imperative to remove them from water effectively. Among feasible alternatives, a composite film made of PVA and kaolin is reviewed for copper removal via an adsorption mechanism. In this paper, the removal of copper ions from aqueous solution using PVA/Kaolin composite film has been studied with initial copper ions concentration within the range of 50 and 100 ppm and pH of the aqueous solution being controlled at 4, 7, and 9. The loading of 3 wt kaolin in PVA shows the best adsorption performance in removing 99.14 of 50 ppm copper with an equilibrium adsorption capacity of 5.379 mg g-1 at pH 7. The composite can maintain the adsorption performance for the removal of 100 ppm copper solution at 96.26. Â© 2022, Gadjah Mada University. All rights reserved.